Preoperative operative optimisation for surgery in a patient with thyrotoxicosis - Jankovska A; Georgiev, A; Kokareva, M; Nedelkova, I; Stojanoski, S; Andov, M; Jovanovski -Srceva, M (MIT Univerzitet, Skopje, 2023)
Thyrotoxicosis as a clinical condition characterized by excessive thyroid hormone activity in the bloodstream, show different effects on different organ systems. Common symptoms include palpitations, tachycardia, tremor, anxiety, weight loss, and if the state is not controlled, extreme and detrimental cardiovascular symptoms may occur. Graves disease, toxic multinodular goiter, toxic adenoma, thyroiditis, and iatrogenic causes are all possible causes of thyrotoxicosis. The patient's heart condition, as well as the possibility of arrhythmias, cardiac ischemia, and congestive heart failure, should be constantly monitored during the intraoperative and postoperative periods. Surgery, trauma, or infection increases the risk of perioperative thyroid storm. Patients with hyperthyroidism who aren't clinically ready for surgery are in grave danger.e present case of 20 year old female patient in witch with good strategy, careful manipulation and good preoperative assessment, we managed to avoid a thyroid storm. There was no apparent perioperative complication.
Keywords: thyrotoxicosis; pre-operative therapy; thyroidectomy